New taxonomic proposal for Chinese phraseology - Chunyi 雷春仪 Lei (Círculo de Lingüística Aplicada a la Comunicación, 2019)
Over the years, the taxonomy of Chinese phraseology has been controversial. One of the main challenges for research in the field of phraseology is to discover how to classify all of the phraseological units in a logical and objective way. Based on the concept of grammatical metaphor (Pamies 2014, 2017), this paper tries to prove that a new taxonomy, more similar to the “Western” tradition, with the criteria of fixedness, idiomaticity and multilexematicity could be applied to the Chinese phraseology. Firstly, we examine the terminological problems in the Chinese phraseology and explain the function of metaphor in phraseology. Secondly, we demonstrate how this new taxonomy is applied to all the categories of Chinese phraseology, offering new terminology and definitions for each category. Thirdly, we focus on the slight taxonomic differences regarding phraseology between Chinese and Romanic/Germanic languages. Hopefully the application of this new taxonomy to Chinese phraseology can facilitate an objective comparison with other languages.